2016
DOI: 10.1002/app.44396
|View full text |Cite
|
Sign up to set email alerts
|

Influence of K+ and Na+ ions on the degradation of wet‐spun alginate fibers for tissue engineering

Abstract: A synthetic type of wet‐spun alginate fibers were immersed in simulated body fluid(SBF) composed of K+, Na+, and Ca2+ cations with various concentrations. Experimental measurements revealed that Na+ had a greater impact on degradability than that of K+ ion. The finding was further confirmed by the characterization of mass loss, ICP, XRD, and theoretical analyses. The degradation process and mechanism were demonstrated through the research on swelling behavior and mass loss. Besides, the wet‐spun alginate fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
(57 reference statements)
1
11
0
Order By: Relevance
“…The composite porous brous dressings were fabricated by a self-developed microuidic spinning system. 39 Three types of brous dressing were marked as: SA (alginate brous dressings), SA-HAP (alginate-hydroxyapatite composite brous dressing), SA-SiO 2 (alginate-silica composite brous dressings) and listed in the Table 1.…”
Section: Fabrication Of Biocomposite Porous Bersmentioning
confidence: 99%
See 1 more Smart Citation
“…The composite porous brous dressings were fabricated by a self-developed microuidic spinning system. 39 Three types of brous dressing were marked as: SA (alginate brous dressings), SA-HAP (alginate-hydroxyapatite composite brous dressing), SA-SiO 2 (alginate-silica composite brous dressings) and listed in the Table 1.…”
Section: Fabrication Of Biocomposite Porous Bersmentioning
confidence: 99%
“…Our previous study found that the degradation of alginate bers initiated from the swelling process. 39…”
Section: Swelling Behavior Of Bersmentioning
confidence: 99%
“…Based on the ability to gel with metal ions, different alginate-based materials with various morphology were developed, such as the porous scaffold [ 9 , 10 , 11 ], hydrogel [ 12 , 13 ], fiber [ 14 , 15 , 16 ], nonwoven fabric [ 17 , 18 ], membrane [ 19 , 20 , 21 ], and so forth. The common way to fabricate the alginate-based materials includes ion cross-linking [ 22 ], microfluidic spinning technique [ 23 ], freeze-drying [ 24 ], wet spinning technology [ 25 ] and immersive rotary/centrifugal jet spinning technique [ 26 , 27 , 28 ]. Recently, alginate hydrogel has been prepared by the freeze-drying technique or ionic cross-linking method.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been applied to address these challenges including functionalization of the scaffolds with bioactive molecules [17,18], combination of various types of biomaterials [19,20], incorporation of chemical ions and molecules [21,22] and nanomaterials [23][24][25][26][27], or a combination of these [28,29]. 3D multifunctional scaffolds are increasingly favored because they can mimic the structure of the natural ECM and provide a condition for the spatial organization of cells and enhancing the cell-cell interactions [7,8,13,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%